A Novel Unusual Manifestation of CH-Alpha as Acute Metabolic Disturbances: Case Report and Big Data Analytics: A Novel Unusual Manifestation of CH-Alpha as Acute Metabolic Disturbances - Al-Imam, Ahmed; Gorial, Fai’q Isho; Al-Shalchy, Ali Kamil (Journal of the Faculty of Medicine Baghdad, 2020)
Background: The pharmaceutical “marketplace” is booming with a plethora of over-the-counter products known as supplements, including regulated and unregulated chemicals that can be purchased from pharmacies, the black market, or via the internet, including the infamous deep web and the darknet. Some supplements can boost specific physiological functions, including physical endurance, sexual performance, and musculoskeletal-articular rejuvenation. Case Report: We are reporting a case of acute metabolic disturbances that materialized following the ingestion of CH-alpha. An otherwise healthy 35 years old male from Iraq, manifested with bilateral periorbital and dependent leg edema. Biochemical profiling revealed hypoproteinemia [6.5 g/dl], hypogammaglobulinemia [1.58 g/dl], hypercholesterolemia [218 mg/dl], and a borderline serum creatinine [1.2 mg/dl]. Following CH-Alpha’s withdrawal, the patient’s condition resolved spontaneously. Although the reported case is anecdotal, we implemented the Bradford Hill’s criteria to analyze its credibility and the implied level-of-evidence in connection with causality. We also carried out collateral analytics of big data, using Google Trends, to infer data on the spatiotemporal variations of the interest of the public in CH-Alpha and related products. Conclusion: Future externally-valid studies, including controlled trials and metanalytic studies, can satisfy the full Hill’s criteria on the potential causality for the observed acute dysmetabolism in humans.